Association Between Traumatic Brain Injury and Dementia in Veterans: A Rapid Systematic Review. Issue 3 (May 2020) - Peterson, Kimberly; Veazie, Stephanie; Bourne, Donald; Anderson, Johanna
Abstract : Objective: To systematically review the prevalence of dementia in Veterans versus civilians and the association between previous traumatic brain injuries (TBIs) and the risk and timing of dementia onset in Veterans. Design: We systematically searched MEDLINE, PsycINFO, and Cochrane Central Register of Controlled Trials from database inception to October 2018. One reviewer assessed articles for inclusion, evaluated study quality, graded strength of evidence, and extracted data, with second reviewer checking. Results: Forty articles were included, among which 10 presented the best evidence. Evidence suggests that dementia rates are likely similar between Veterans and civilians (10.7% vs 8.8%-11.6%, respectively). Dementia prevalence is likely higher in those with TBI (6%-16%) than in those without (3%-10%), with a possible dose-response relationship between the two. There may also be an association between TBI and early-onset dementia, although this evidence has important limitations. No studies evaluated whether dementia prevalence varied on the basis of combat deployment history or era of conflict. Conclusion: Dementia prevalence is likely similar in Veteran and civilian populations, and the risk of dementia is likely increased by TBI. To inform development of screening, prevention, and rehabilitation efforts, research is still needed addressing the mechanism of association and timing of dementia onset. Protocol: PROSPERO; CRD42018107926.